Valorization of olive pomace with subcritical water - Gameiro, Rita Alexandra Pereira (2016)
All over the world large quantities of agro-industrial waste are produced, which accumulate over the years, causing serious environmental problems and a devaluation of this promising biomass because it is cheap and has great potential, since it produces a wide range of products when it is processed. An example is the olive pomace (OP), a byproduct of the olive oil industry, characterized by being a very humid sludge, composed of a mixture of skin, flesh and seeds from the olives. In addition to oil, this residue contains antioxidants with potential added value for the cosmetics, food and pharmaceutical industries. The objective of this study, is to explore the PO's potential as a source of antioxidants, by extracting these compounds with subcritical water. In parallel, the partial hydrolysis of this residue also takes place, obtaining a sugar rich liquor. For the purpose of homogenization, the PO was divided into two samples, Fine Sample (FS) and Gross Sample (GS). The GS consisted mainly of seeds residues from olive, and the particles had diameters above 1400 micrometers. Before the extraction, both samples were chemically characterized. It was found that FS had a higher content of lipids (about 55%) and soluble sugars (about 5%). On the other hand, the GS had higher levels of insoluble sugar (about 23%) and lignin (60%). The polyphenol content obtained for both samples was less than 1%, and hydroxytyrosol was the most abundant phenolic compound. The extraction/hydrolysis was performed only for FS in order to optimize the process, the temperatures used were 140, 170 and 200°C. The water flow and pressure were maintained constant, 10 mL/min and 60 bar, respectively. The best results were obtained at 200 °C, with a yield of soluble compounds of 30%. It was possible to extract 20.87 mg/g of phenolic compounds and a recovery of sugars of 14% wt., relative to the existing, 18.12%. It was also determined the antioxidant activity of extracts obtained in each assay, the best result was obtained for the extracts, at 200 °C, having been obtained an EC50 =32.83 mg/L. It also studied the stability of phenolic compounds as well as antioxidant activity. As expected, through time, the phenolic compounds will be degraded, and is more pronounced when these compounds are exposed to light and at room temperature.